Handbook of Glaciers & Glacier Retreat - Fonseca, Machelle, author 640248; Leorne, Clyde, author 650755 (Delhi, India : Academic Studio, 2012)
This is a well written thorough Handbook of Glaciers & Glacier Retreat.